Why is mannitol becoming more and more popular as a pharmaceutical excipient in solid dosage forms?. (May 2014) - Ohrem, H. Leonhard; Schornick, Eva; Kalivoda, Adela; Ognibene, Roberto
Abstract Various fillers/binders which are applied for the formulation of solid oral dosage forms are assessed for their benefits and drawbacks, including lactose, sorbitol, mannitol, microcrystalline cellulose and calcium hydrogen phosphate dihydrate. A focus of this work was to evaluate the application of mannitol in comparison to other common fillers/binders as it was observed that this excipient is gaining more and more attention in pharmaceutical formulation development and production. While one of the main advantages of conventional fillers/binders such as lactose, microcrystalline cellulose and calcium hydrogen phosphate dihydrate is their low price level, mannitol excels regarding its physicochemical characteristics such as a low hygroscopicity, a strong inertness towards both the API and the patient's body, its good compactibility and the ability to produce extremely robust tablets. Additionally, the suitability of mannitol for the emerging formulation technology of orally disintegrating tablets is pointed out. In summary, it is emphasized that the selection of the filler/binder is highly individual, depending, for example, on the preferred characteristics of the final solid dosage form, the applied API and the available budget. However, mannitol exhibits many strong advantages which can be expected to result in a more widespread application in the near future.